Non catalytic methane formation from syngas in the dielectric barrier discharge plasma, initiated by microsecund pulses; Energy Fluxes and Radiation Effects (EFRE-2016) - Litvishko E. S. Evgeniy Sergeevich (2016, 2016)
Title screen